Efektivitas Timeschedule dan Progres Monitoring Pekerjaan pada Nusantara Maintance Facilites (NMF) PG Djombang Baru : Studi pada Nusantara Maintance Facilites (NMF) PG Djombang Baru - Mista Octavia; Ety Dwi Susanti (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
The report aims to evaluate the effectiveness of the Timeschedule and also the progress of the operational activities of Nusantara Maintenance Facilities (NMF). The results of the internship implementation show that the application of the Timeschedule and progress play an important role in maintaining effectiveness and efficiency of the work in achieving operational targets.